ANALISIS PELAKSANAAN PROMOTION MIX DAN PENGARUHNYA TERHADAP KUALITAS DAYA SAING USAHA (STUDI KASUS UMKM BERBASIS INDUSTRI KREATIF BINAAN PT. TELKOM CDC AREA MEDAN) - Nasruddin Nasruddin; Ika Agustina (JURNAL ILMIAH MANAJEMEN & BISNIS, 2015)
The results showed that, Advertising is the most frequently promotional device used by creative industries. From 30 creative Industries, there were 26 (86.67%) who used advertising to promote their products. Moreover, advertising also has the most dominant influence on the quality of the creative industry's competitiveness. Partially, among the five types of existing promotion mix; advertising, personal selling and sales promotion are promotion mix that significantly affect the quality of the creative industry's competitiveness. they are proven to improve productivity, profitability and broad market coverage of the creative industries. Meanwhile, public relations and direct marketing do not affectpositevely on the quality of the creative industry competitivenessKata Kunci: Promotion Mix, Daya Saing, Industri Kreatif